2020
DOI: 10.1186/s13037-020-00272-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and root causes of surgical site infections after gastrointestinal surgery at a public teaching hospital in Sudan

Abstract: Background Surgical site infections (SSIs) are common healthcare-associated infections and associated with prolonged hospital stays, additional financial burden, and significantly hamper the potential benefits of surgical interventions. Causes of SSIs are multi-factorials and patients undergoing gastrointestinal tract procedures carry a high risk of bacterial contamination. This study aimed to determine the prevalence, associated factors, and causing microorganisms of SSIs among patients underg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
7
15
0
Order By: Relevance
“…The current literature shows wide range of variability regarding the rates of laparotomy related ISSI (21)(22)(23)(24) . Thus, the rate of ISSI in our study was almost similar to study (25) and relatively close to others which reported ISSI rate of 22.6% (21) and 21% (22) . However, our results were obviously lower than Sumi et al (23) (36.2%) and higher than Zaidi and co-workers (13.8%) (26) .…”
Section: Discussionsupporting
confidence: 91%
“…The current literature shows wide range of variability regarding the rates of laparotomy related ISSI (21)(22)(23)(24) . Thus, the rate of ISSI in our study was almost similar to study (25) and relatively close to others which reported ISSI rate of 22.6% (21) and 21% (22) . However, our results were obviously lower than Sumi et al (23) (36.2%) and higher than Zaidi and co-workers (13.8%) (26) .…”
Section: Discussionsupporting
confidence: 91%
“…This is significant because blood loss is linked to poor tissue oxygenation, which contributes to the development of SSI. Also, as previously observed [29,30], intraoperative hypotension is closely linked to SSI, and this is due to the inadequate wound perfusion caused by intra-operative hypotension [27].…”
Section: Developmentmentioning
confidence: 55%
“…Another study found that 26.1 percent of patients who had severe intra-operative blood loss had wound infection [27,28]. There is a significant link between SSI and intra-operative blood loss of more than 500 ml.…”
Section: Developmentmentioning
confidence: 99%
“…Overall, Staphylococcus aureus is one of the most common microbes being found in SSI, followed by typical gut commensals such as Escherichia coli and Enterococcus faecalis [2,100]. In visceral surgery, Gram negative bacilli as well as facultative anaerobes are the most common origin of SSI [4,10,11,[101][102][103]. Most of the pathogens are normal inhabitants of the human body making it debatable why some patients develop SSI and others not.…”
Section: Research Question 3: the Relation Between The Gut Microbiota And The Development Of Surgical Site Infectionsmentioning
confidence: 99%